2002
DOI: 10.1177/027112140202200102
|View full text |Cite
|
Sign up to set email alerts
|

Embedding and Distributing Constant Time Delay in Circle Time and Transitions

Abstract: The purpose of this study was to evaluate embedding and distributing constant time delay instructional trials into circle time activities and transitions between activities. Three boys in a summer day camp participated, and their teachers implemented the instruction. A multiple probe design across behaviors and replicated across participants was used. The data indicated (a) the teachers embedded and distributed the instruction accurately; (b) the children acquired the behaviors they were taught; (c) the trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 19 publications
2
33
0
2
Order By: Relevance
“…When used in general education contexts the use of distributed trials is called embedded instruction (McDonnell, Johnson, & McQuivey, 2008). Numerous studies have examined the use of embedded instruction to teach specific skills to students with severe disabilities (Jameson, McDonnell, Johnson, Riesen, & Polychronis, 2007;McDonnell, Johnson, Polychronis, & Riesen, 2002;Wolery et al, 2002). For example, Johnson and McDonnell (2004) examined the effects of teacher-delivered embedded instruction in a general education elementary classroom on core content with three students with moderate intellectual disability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When used in general education contexts the use of distributed trials is called embedded instruction (McDonnell, Johnson, & McQuivey, 2008). Numerous studies have examined the use of embedded instruction to teach specific skills to students with severe disabilities (Jameson, McDonnell, Johnson, Riesen, & Polychronis, 2007;McDonnell, Johnson, Polychronis, & Riesen, 2002;Wolery et al, 2002). For example, Johnson and McDonnell (2004) examined the effects of teacher-delivered embedded instruction in a general education elementary classroom on core content with three students with moderate intellectual disability.…”
mentioning
confidence: 99%
“…One potential challenge in embedding this instruction is the amount of trials needed to ensure student progress (Wolery et al, 2002). Most of the research on constant time delay and embedded instruction has involved acquisition of two or more behaviors with at least five trials per behavior per lesson.…”
mentioning
confidence: 99%
“…After a predetermined number of 0-seconddelay trials, the instructor inserts a fixed amount of duration (i.e., 4 or 5 seconds) between the task directions and the prompts (Browder & Snell, 2000;Schuster et al, 1998;Wolery, Ault, & Doyle, 1992). A considerable number of research studies has shown that CTD is effective in teaching both discrete and chained skills to young children with various disabilities (e.g., Alig-Cybriwsky, Wolery, & Gast, 1990;Daugherty, Grisham-Brown, & Hemmeter, 2001;Halle, Bear, & Spradlin, 1981;Werts, Wolery, Vassilaros, & Billings, 1992;Wolery, Anthony, Caldwell, Snyder, & Morgante, 2002).…”
mentioning
confidence: 99%
“…(See Snyder et al, in press, for a full description). EI is considered a preferred instructional practice for children with ASD because it occurs during naturally occurring activities throughout the child's day, in contexts in which the child is to engage in that skill in the future and targets essential learning goals (barton, Lawrence, & Duerloo, 2012;Heflin & Isbell, 2012;wolery, Anthony, Caldwell, Snyder, & Morgante, 2002). These characteristics are consistent with the nrC guidelines (nrC, 2001) as well as naturalistic interventions, an evidence-based FIP for learners with ASD (See odom, Collet-klingenberg, et al, 2010).…”
Section: Embedded Instruction (Ei)mentioning
confidence: 90%